Problematika Pembelajaran Bahasa Arab dengan Menggunakan Metode Ceramah Interaktif di Sekolah Tahfizh Tingkat Dasar (STTD) Al Hikam Surakarta - Nafa Khusnul Ummah (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2022)
This study aims to improve the teaching and learning achievement of Arabic in Class VA of STTD Al Hikam Surakarta by using the Interactive Lecture Method, to identify the problems that occur in Arabic learning in Class VA using the Interactive Lecture Method, and to understand the significant impact of the interactive lecture method on the learning achievement of Class VA students at STTD Al Hikam Surakarta. The results of the study show that in Class VA of STTD Al Hikam Surakarta, Arabic learning using the Interactive Lecture Method is still conducted with conventional or old methods, and the application of the interactive lecture method in Class VA has not yet been successful. This is due to several factors, including the teacher's mastery of the material and methods, as well as the students’ readiness, which is greatly influenced by factors such as intelligence, the child's psychological state, and family background. Additionally, the supporting facilities and infrastructure are still inadequate.